A cross-sectional analysis of the effectiveness of a nutritional support programme for people with tuberculosis in Southern Madagascar using secondary data from a non-governmental organisation - Franke, Mara Anna; Emmrich, Julius; Ranjaharinony, Fierenantsoa; Ravololohanitra, Onja Gabrielle; Andriamasy, Harizaka Emmanuel; Knauss, Samuel; Muller, Nadine (Infectious diseases of poverty, 2024)
Background: There is a strong, bi-directional link between tuberculosis (TB) and undernutrition: TB often causes undernutrition, and undernourished people are more likely to contract TB and experience worse outcomes. Globally, several TB nutritional support programmes exist; however, evidence on their effectiveness is limited and contested. This study evaluates the effect of a nutritional support programme implemented for people with TB in the Atsimo-Andrefana region, Madagascar in 2022. Within this programme, undernourished people with TB [with a body mass index (BMI) of < 18.5 kg/m2] receive 0.6 L of vegetable oil and 6.0 kg of a soy-wheat blend per month throughout their TB treatment. Methods: We analysed secondary non-governmental organisation data collected between January and November 2022 in the Atsimo-Andrefana region, Southern Madagascar, including information on an individual’s medical conditions (e.g., type of TB, treatment outcomes) and nutritional status measured prior to, during, and after completion of treatment (e.g., height, weight, mid-upper arm circumference). We conducted descriptive analyses of patient baseline characteristics and outcomes to assess the impact of the provided nutritional support on the BMI of people with TB. Results: A total of 1310 people with TB were included in the study [9.9% (130) children under the age of 5, 32.1% (420) children between 5 and 18 years, 58.0% (760) adults]. 55.4% of children under 5, 28.1% of children between ages 5 and 18, and 81.3% of adults were undernourished at treatment initiation. 42.3% (55/130) of children under 5 experienced severe acute malnutrition at treatment uptake. While the average BMI of adults with TB receiving food support increased over time, from 17.1 kg/m2 (interquartile range: 15.8–18.3, range: 10.3–22.5) to 17.9 kg/m2 (interquartile range: 16.6–19.1, range: 11.9–24.1), most adults remained undernourished even after completing TB treatment. Conclusions: The current TB nutritional support programme falls short of sufficiently increasing the BMI of people with TB to overcome malnutrition. There is an urgent need to revise the nutritional support available for people with TB, particularly for children under 5.